Hepatitis C virus genotypes in Saudi Arabia: a future prediction and laboratory profile - Bawazir, Amen (Virol J, 2017)
BACKGROUND: Hepatitis C virus (HCV) genotypes and subtypes are considered an important tool for epidemiological and clinical studies and valuable markers for disease progression and response to antiviral therapy. The aim of this study was to identify the prevalence of HCV genotypes and their relation to socio-demographic factors particularly age and sex, various biochemical profiles and viral load. METHODS: The records (630) of Saudi patients positive for HCV (2007–2011) reported in the system of the Molecular Pathology Laboratory at a tertiary reference hospital in Riyadh, Saudi Arabia were analyzed. Socio-demographic characteristics, liver biochemical profile, viral load and co-infection with HBV and HIV were retrieved from the hospital database. The associations of continuous and categorical variables with genotypes were analyzed. RESULT: The overall mean age of the surveyed patients was 59 years ±0.5 years (21% were <50 years (p = 0.02). The rate of infection is lower in males than in females (47.6% vs. 52.4%). HCV genotype 4 was the most prevalent (60.7%), followed by genotype 1 (24.8%). However, genotype 1 and 3 were found more in males (29.7% vs. 20.3% and 6% vs. 2.1%, respectively, p = 0.001), while genotype 2 and 4 were more among females (4.8% vs. 2% and 68.5% vs. 52.3%, respectively). In addition, genotype 1 was found dominant in younger males (33.8%). Biochemical parameters across gender showed significant variation in particular for the ALT (p = 0.007). The mean viral load was significantly higher in genotype 1 than genotype 4 (4,757,532 vs. 1,435,012, p = <001). There is a very low overall percentage of co-infection of HBV or HIV in this study (around 2% for each). CONCLUSION: Although HCV genotype 4 shows an overall high prevalence in this study, a clear decline in the rate of this genotype was also demonstrated in particular among the younger age group who displayed increasing trends toward the global trend of genotype 1, rather than genotype 4. This finding would be of clinical interest in relation to future planning of the therapy for HCV infected patient.